2015
DOI: 10.1093/cid/civ808
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Vancomycin and β-Lactam Therapy for Methicillin-ResistantStaphylococcus aureusBacteremia: A Pilot Multicenter Randomized Controlled Trial

Abstract: Combining an antistaphylococcal β-lactam with vancomycin may shorten the duration of MRSA bacteremia. Further trials with a larger sample size and objective clinically relevant end points are warranted. Australian New Zealand Clinical Trials Registry: ACTRN12610000940077 (www.anzctr.org.au).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 27 publications
4
133
1
1
Order By: Relevance
“…A retrospective study found a higher rate of clearance of MRSA bacteremia in patients receiving empiric vancomycin plus a β-lactam than in patients receiving vancomycin alone [30]. A pilot randomized clinical trial comparing an antistaphylococcal β-lactam in combination with vancomycin to vancomycin alone found that the duration of MRSA bacteremia was shorter by about a day 3.00 days with vancomycin alone versus 1.94 days with the combination [31]. There is a lack of evidence of benefit of vancomycin combined with other antistaphylococcal antibiotics.…”
Section: Combination Therapymentioning
confidence: 99%
“…A retrospective study found a higher rate of clearance of MRSA bacteremia in patients receiving empiric vancomycin plus a β-lactam than in patients receiving vancomycin alone [30]. A pilot randomized clinical trial comparing an antistaphylococcal β-lactam in combination with vancomycin to vancomycin alone found that the duration of MRSA bacteremia was shorter by about a day 3.00 days with vancomycin alone versus 1.94 days with the combination [31]. There is a lack of evidence of benefit of vancomycin combined with other antistaphylococcal antibiotics.…”
Section: Combination Therapymentioning
confidence: 99%
“…In a retrospective cohort monocentric study of patients with MRSA bacteremia, those who received vancomycin plus one β-lactam were more likely to experience microbiological eradication of MRSA than patients who received vancomycin alone [14]. More recently, in a pilot multicenter RCT for MRSA bacteremia [15], patients received vancomycin 1.5 g IV twice daily and were randomly assigned to flucloxacillin 2 g IV 6 hourly for 7 days or no additional therapy. The combination therapy group showed shorter duration of MRSA bacteremia and there was no difference in 28-and 90-day mortality, metastatic infection, nephrotoxicity, or hepatotoxicity (Table 1).…”
mentioning
confidence: 99%
“…Furthermore, recent support for combination therapy comes from an open‐label, multicentre clinical trial in Australia that randomized 60 patients with MRSA bacteraemia to receive vancomycin (n = 29) or vancomycin in combination with flucloxacillin (n = 31). Although there was no difference in mortality and metastatic infection, the mean duration of bacteraemia in the combination therapy group was 1.94 days compared to 3 days in the standard group (ratio of means 0.65, 95% CI 0.41‐1.02) . Another retrospective study which evaluated 97 patients demonstrated similar outcomes in which β‐lactam plus vancomycin combination compared to vancomycin monotherapy resulted in improvements to bacteraemia clearance (median time to clearance of 3 days vs 4 days, respectively, P = 0.047) with no improvements in treatment failures (24.6% vs 30%, respectively, P = 0.55) .…”
Section: Resultsmentioning
confidence: 94%